The Relationship between Team Competency and Design Risk Management among Construction Industries in Kuantan - Nur Dini, Jamil; Adeleke, A. Q. (Penerbit Akademia Baru, 2018)
This paper assessed the relationship between team competency and design risk management among Kuantan construction industries. Similarly, a survey was conducted among 10 local and national construction industries in Kuantan with a stratified random sampling. The returned questionnaires yielded 10 responses which was used for data analysis. Five point Likert scale categories of risk management from the previous studies was used and statistical analysis affirmed that there is positive relationship between team competency and design risk management among Kuantan construction industries.